1997
DOI: 10.1097/00019606-199704000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hepatitis C by RT-PCR in Formalin-Fixed Paraffin-Embedded Tissue from Liver Transplant Patients

Abstract: The histopathologic alterations of hepatitis C virus (HCV) infection of the liver overlap with those of other diseases, making interpretation of liver biopsy specimens in some cases insufficient to render a diagnosis. Although HCV infection can be confirmed by detection of circulating anti-HCV antibodies, immunocompromised liver transplant recipients are often unable to mount an immunologic response to the virus, resulting in false-negative serologic testing. We describe the comparison of reverse transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…20 Another study showed that 8 to 24 hours of formalin fixation leads to loss of RNA by a factor of 100 to 1,000. 21 However, long-term paraffin storage has not been shown to be deleterious in the preservation of HCV RNA. In our study, specimen fixation was consistently less than 8 hours; therefore, we are confident there has been minimal degradation of HCV RNA in the tissues studied.…”
Section: Discussionmentioning
confidence: 99%
“…20 Another study showed that 8 to 24 hours of formalin fixation leads to loss of RNA by a factor of 100 to 1,000. 21 However, long-term paraffin storage has not been shown to be deleterious in the preservation of HCV RNA. In our study, specimen fixation was consistently less than 8 hours; therefore, we are confident there has been minimal degradation of HCV RNA in the tissues studied.…”
Section: Discussionmentioning
confidence: 99%
“…There was no evidence of HIV infection in our cases All the samples were reevaluated by an expert pathologist (ME) and classified according to the REAL classification [12]. The Enhanced Avian RT-PCR Kit (Sigma, St. Louis, MO) was used both in tissue and in serum in order to obtain HCV-RNA.…”
Section: Methodsmentioning
confidence: 99%
“…Tordji-22 has recently been used to detect HCV antigens in both nontransplant 19,20 and posttransplantation liver tissue. 20,21 Initially, our results indicated a strong correlation between the location of HCV antigens and areas of liver injury, particularly regions of hepatocyte ballooning. Further testing showed cross-reaction of this monoclonal antibody with host epitopes present in non-HCV liver transplant tissue.…”
Section: Copyright 1999 By the American Association For The Study Of mentioning
confidence: 67%
“…[19][20][21]30 Therefore, the claim that this monoclonal antibody detected HCV antigen in severely damaged liver tissue from a case of fulminant hepatitis must be viewed with caution. 19 In support of our finding, other groups have reported that the commercial monoclonal antibody Tordji-22 has been associated with both low sensitivity 21,31 and nonspecificity 32 when tested on chronic HCV-infected patients and HCV-positive liver allograft recipients. Vartanian et al 30 observed diffuse, cytoplasmic staining of biopsy specimens from patients with HCV, HBV, and nonviral liver disease tested with Tordji-22.…”
Section: Discussionmentioning
confidence: 99%